The First Documenta in Kassel (1955) and the Problem of a Conceptualized Art History - Bulatov, Danila A. (Actual Problems of Theory and History of Art, 2013)
In this article we are discussing the problem of the appearance of a conceptualized art history by the example of the first documenta exhibition held in Kassel, Germany, in 1955. It was an out-standing cultural event of that time and it was used for legitimating contemporary artistic practices, which continued the tradition of the so-called “classical modernity”. It also had promoted the reintegration of West Germany into Europe-wide art context. Moreover, among other important institutions oriented to contemporary art in the second part of the 20th and the beginning of the 21st centuries, documenta took part in the formation of practically homogeneous international art space. At the same time it should be noted, that the breach of this trend can already be traced in the concepts of the two latest documenta-exhibitions (2007 and 2012), which are testifying the desire to overwhelm the singularity of an up-to-date mainstream of art history.
Keywords: art history; modernist Revival; the Cold War; West Germany; exhibition practice; classical modernity; art institutions; documenta